Cholecystitis and nephrotic syndrome complicating Epstein–Barr virus primary infection. (2nd January 2017) - Rodà, Diana; Huici, Malka; Ricart, Sílvia; Vila, Jordi; Fortuny, Clàudia; Alsina, Laia
Abstract : Epstein–Barr virus (EBV) infection results in a spectrum of clinical manifestations. The host immune response to EBV plays a key role in the extent and degree of clinical features, which in children under 4 years of age are usually mild, non-specific and self-limiting. A 2-year-old boy in whom no known immune disorder could be found presented with acute acalculous cholecystitis, renal dysfunction with massive proteinuria, ascites, pleural effusion, minimal peripheral oedema and a severe systemic inflammatory response. Improvement occurred after initiation of corticosteroids and antiviral treatment with gancyclovir. In severely symptomatic or complicated EBV infection, a primary immunodeficiency must be suspected. If a primary immunodeficiency has been ruled out, the correct management of severe EBV infection in the immunocompetent host remains controversial.